Asymptotic Numerical Method for strong nonlinearities - Zahrouni, Hamid; Aggoune, Wassila; Brunelot, Juliette; Potier-Ferry, Michel (European Journal of Computational Mechanics, 2004)
Plastic constitutive laws and frictional contact conditions induce strong nonlinearities that one has to take into account in the numerical simulation of material forming processes. In this work, we present a review of the different techniques which permit the asymptotic numerical method (ANM) to be adapted to these nonlinearities. ANM needs regular relations and quadratic equations if possible. Several examples show the effectiveness of the proposed method.